Model Pembelajaran Servis Bawah Bola Voli Untuk Usia SMP - Rudi, Rudi (Jurnal Educatio, 2016)
THE LEARNING MODEL OF VOLLEYBALL UNDER SERVICE  FOR JUNIOR HIGH SCHOOL AGE  RUDI ABSTRACT                The purpose of this research and development is to produce the learning model of volleyball under service for junior high school age. In addition, research and development is conducted to obtain in-depth information about the development and application of the learning model of volleyball under service for junior high school age and determine the effectiveness, efficiency and attractiveness of the model created child. This research uses development methods research & development (R & D) from Borg and Gall. Subjects in research and development are the students of junior high school consisting of 60 children.               The Instruments that used in this research and development is a questionnaire, as well as the instrument volleyball service test that used to collect the volleyball under service data for junior high school age. as for the stages in research and development are: (1) analysis of needs, (2) the expert evaluation (initial product evaluation); (3) limited trial (small group testing); and (4) the main trial (field testing). The effectiveness model test used under service test to know the level of volleyball under service ability for junior high school age before giving treatment such as under service model that developed and to determine the under service ability after treatment or under service treatment that developed, from the initial tests were conducted obtained the student under service level are 3956, then after being given treatment in the form of under service model. The student under service obtained the ability level are 5572. Accordingly this volleyball under service mode is effective to raise the learning model of volleyball under service for junior high school age.               Based on the results of the development can be concluded that: (1) whit the volleyball learning model under service for junior high school age can be developed and applied in physical education learning at schools (2) the volleyball learning model under service for junior high school age which have been developed, acquired evidence of this improv went is shown in the result testing data from pretest and posttest ther is significant difference between before and after the development of a model. Keywords: Development, Model, Under Service